O princípio metafísico da poética de Aristóteles - Angelo, Aurélia Sotero (2005)
Aristotle's definition of tragedy indicates a metaphysical project insinuated by a notion of kátharsis. The reconstruction of Aristotle's method of definition is inspired in the concepts of enérgeia and dýnamis taken from Physics, understanding cause as substance. The Doctrine of the Four Causes is the theoretical basis of the definition of tragedy, placing tragedy in the genre of imitation and distinguishing its species: language (material cause), noble and complete action (formal cause), actors (efficient cause) and kátharsis (temporarily identified with the final cause). Nevertheless, there is no final cause in the definition of tragedy. The kátharsis of passions is experienced by the spectator when he witnesses tragedy, which is the imitation of a noble action, executed by actors and not narrated. Aristotle justifies hid proposition in favor of mimesis by assuming that imitation is natural to man since infancy and the view of objects allows whoever contemplates them to identify and learn the originals. As a metaphysical principle, kátharsis is projected to beyond definition of tragedy, where it is manifested cathartically, in the spectator. Research about the spectator brings one back to the definition of tragedy, where the imitation is an imperfect copy which evokes in the spectator the presence of the originals of the imitated sentiments, thus realizing the kátharsis of these emotions. In this way kátharsis reveals itself as selfknowledge and approach of divine truth and perfections.